2023
DOI: 10.1186/s12967-023-04138-y
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between micronutrient status, frailty, systemic inflammation, and clinical outcomes in patients admitted to hospital with COVID-19

Abstract: Background Micronutrients have been associated with disease severity and poorer clinical outcomes in patients with COVID-19. However, there is a paucity of studies examining if the relationship with micronutrient status and clinical outcomes is independent of recognised prognostic factors, specifically frailty and the systemic inflammatory response (SIR). The aim of the present study was to examine the relationship between micronutrient status, frailty, systemic inflammation, and clinical outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Several reviews have indicated the important roles of micronutrients in immune response [18,20,32,80,87,125], with these roles also applying to the treatment of COVID-19 [20,87,126,127]. Deficiencies of these micronutrients have been reported in increased infection and severity of COVID-19 [128][129][130][131][132].…”
Section: The Corona Virus Disease: Can Micronutrients Help?mentioning
confidence: 99%
“…Several reviews have indicated the important roles of micronutrients in immune response [18,20,32,80,87,125], with these roles also applying to the treatment of COVID-19 [20,87,126,127]. Deficiencies of these micronutrients have been reported in increased infection and severity of COVID-19 [128][129][130][131][132].…”
Section: The Corona Virus Disease: Can Micronutrients Help?mentioning
confidence: 99%